Screening of Graves' disease susceptibility genes by whole exome sequencing in a three-generation family - Zhuoqing Hu; Wei Li; Miaosheng Li; Hao Wei; Zhihui Hu; Yanting Chen; Ai Luo; Wangen Li (BMC, 2021)
Abstract Background Graves' disease(GD) has a tendency for familial aggregation, but it is uncommon to occur in more than two generations. However, little is known about susceptibility genes for GD in the three-generation family. Methods DNA were extracted from three-generation familial GD patient with a strong genetic background in a Chinese Han population. The Whole Exome Sequencing (WES) was utilized to screen the genome for SNVs associated with GD and the Sanger Sequencing was used to confirm the potential disease-causing genes. Results In the case study, there were five patients with Graves' disease(GD) from a three-generation family. The SNVs of MAP7D2(c. 452C > T: p. A151V), SLC1A7(c. 1204C > T: p. R402C), TRAF3IP3(c. 209A > T: p. N70I), PTPRB(c. 3472A > G: p. S1158G), PIK3R3(c. 121C > T: p. P41S), DISC1(c. 1591G > C: p. G531R) were found to be associated with the familial GD and the Sanger sequencing had confirmed these variations. Furthermore, PolyPhen-2 score showed that the variants in TRAF3IP3, PTPRB, PIK3R3 are more likely to change protein functions. Conclusion The MAP7D2, SLC1A7, TRAF3IP3, PTPRB, PIK3R3, DISC1 may be the candidate susceptibility genes for familial GD from a three generations family.